A Review of the Vitamin A Supplementation Program in India: Reasons for Success in the States of Bihar and Odisha. (June 2014) - Rah, Jee H.; Houston, Robin; Mohapatra, Biswajit D.; Kumar, Shri Sanjay; Saiyed, Farhat; Bhattacharjee, Sourav; Aguayo, Victor M.
Background: Preventive vitamin A supplementation (VAS) is an essential child survival intervention. In India, VAS program coverage has remained relatively low, with wide interstate variation. Objective: To review the VAS program in India, particularly in Bihar and Odisha, the two states that have had the most successful VAS programs, to define best practices and identify critical success factors. Methods: A thorough review of existing relevant literature was carried out, supplemented by field visits and interviews with selected partners. Results: Both states have adopted a biannual approach to reach out to children 1 to 5 years of age with VAS every 6 months, while infants below 1 year of age receive their first VAS dose with the measles immunization at 9 months. The critical success factors for the VAS program in the two states include strong leadership and ownership by the state government; close coordination between the two departments that are involved in the VAS program; effective microplanning prior to each biannual round; flexible dosing mechanisms that enhance coverage in hard-to-reach areas; a stable procurement and distribution mechanism to ensure an adequate, timely, and sustainable supply of VAS; intensive social mobilization and communication; and appropriate training and supervision of staff. Conclusions: The governments of Bihar and Odisha have demonstrated that it is feasible to implement a successful and inclusive VAS program in India. The challenge now is to reach out to the remaining 30% to 40% of children who are undoubtedly the hardest to reach and potentially the most vulnerable.